PS02.122: PREOPERATIVE CHEMOTHERAPY WITH BIWEEKLY DOCETAXEL, CISPLATIN, AND 5-FLUOROURACIL FOR ADVANCED ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2018) - Endo, Fumitaka; Akiyama, Yuji; Iwaya, Takeshi; Nikai, Haruka; Umemura, Akira; Baba, Shigeaki; Chiba, Takehiro; Kimura, Toshimoto; Takahara, Takeshi; Otsuka, Koki; Nitta, Hiroyuki; Mizuno, Masaru; et al.
Abstract: Background: Docetaxel, cisplatin, and 5-fluorouracil (DCF) therapy can have severe adverse events, including neutropenia and febrile neutropenia. Feasibility of DCF is a concern especially for elderly patients, patients with moderate organ disorder, and those with dysphagia or insufficient oral intake causing malnutrition. We introduced biweekly DCF therapy (bDCF) for the purpose of reducing severe adverse events for these fragile patients. This study investigated the feasibility and efficacy of bDCF therapy for patients with advanced esophageal squamous cell carcinoma who underwent radical esophagectomy after chemotherapy. Methods: The parent DCF regimen consisted of 60–70 mg/m 2 of docetaxel on day 1, administered intravenously for 2 h; 80 mg/m 2 of cisplatin on day 1, administered intravenously for 2 h; and 5-fluorouracil administered by continuous infusion at a dose of 800 mg/m 2 on days 1–5. The DCF regimen was repeated every 3–4 weeks. The bDCF regimen consisted of docetaxel (30 mg/m 2 ) on days 1 and 15 in combination with cisplatin (80 mg/m 2 on day 1) and 5-fluorouracil (800 mg/m 2 on days 1–5), repeated every 4 weeks. Results: Thirty-seven patients were treated with the DCF regimen (DCF group) and 22 patients were treated with the bDCF regimen (bDCF group). The age of patients was significantly higher in the bDCF group than in the DCF group. The bDCF group had more patients with heart and pulmonary comorbidities. Biweekly DCF group was significantly higher in the clinical response rate (DCF group 62.2% vs. bDCF group 86.4%, P = 0.0472). Grade 3 or 4 neutropenia was less frequent in the bDCF group (40.9%) than in the pDCF group (81.1%) ( P = 0.0016). Among non-hematologic toxicities, anorexia was less frequent in the bDCF group (0%) than in the pDCF group (18.9%) ( P = 0.0298). There were no significant differences between the groups in postoperative morbidity rate (bDCF group 45.5% vs. pDCF group 32.4%). Conclusion: Preoperative bDCF therapy was feasible and safety without reduction of the efficacy of DCF therapy for fragile patients such as elderly patients, patients with moderate functional disorder, and that with malnutrition caused by dysphagia or insufficient oral intake. Disclosure: All authors have declared no conflicts of interest.